Controling the Abandoned Land in Tegal Regency - S Sudjito; Mohammad Paurindra Ekasetya (Jurnal Dinamika Hukum, 2019)
This research aims to know and to analyze the cause of Abandoned land in Sumbarang village, Tegal regency, the effort which has been done by land office of Tegal regency and the obstacle which is faced by the Tegal Regency’s Land Office in controling the Abandoned land. The type of this research is an empirical law which placed in Sumbarang village, Tegal regency. The source of the data consist of primary and secondary data. It is analyzed by qualitative technique. The results of this research find that the factors of the Abandoned land in Sumbarang village are: (1) the wide of the land is not comparable with the worker (2) the right land is lended to Sugar Company (PG) Pangkah, so the farm is changing function. (3) plant hama attack. The efforts which is done by the land office of Tegal regency toward the Abandoned land are (1) directing the right holder to use their land. (2) monitoring towards the land right, (3) evaluating the land right (4) controling based on Government Regulation Number 11 of 2010 jo. Regulation of the Head of the National Land Agency Number 4 of 2010. The Tegal office land faces some obstacles, they are (1) the right holder lives is unknown, so, it causes difficulty in giving the warn. (2) the right holder is not cooperative. There is no coordination and coorperation betwen the right holder and land Office.Keywords: Controling, Abandoned Land, Tegal Regency